2021
DOI: 10.1111/ijcp.14631
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dyspnea severity and sleep quality in patients with novel coronavirus

Abstract: Aim Dyspnea, a common symptom of novel coronavirus, can negatively affect sleep quality. The aim of this study was to evaluate the relationship between dyspnea severity and sleep quality in patients with COVID‐19. Study Design A cross‐sectional design was used. Methods Using the researcher's mobile phone, data were collected via an online questionnaire from patients (n = 100) who agreed to participate in the study. The data‐collection form co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Consistent with our results, in a study conducted on patients with novel coronavirus, it was reported that there was a relationship between SQ scores and SF-36 subscales such as physical functioning, energy and vitality, mental health and social functioning. 27 The Short-Form 36 questionnaire is a tool used to determine QOL. Several studies have investigated relationship between adherence to MD and SF-36 scores.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, in a study conducted on patients with novel coronavirus, it was reported that there was a relationship between SQ scores and SF-36 subscales such as physical functioning, energy and vitality, mental health and social functioning. 27 The Short-Form 36 questionnaire is a tool used to determine QOL. Several studies have investigated relationship between adherence to MD and SF-36 scores.…”
Section: Discussionmentioning
confidence: 99%